Optimization of chromatic dispersion measurement technique using relative power of two beating frequencies - Abdul Rashid, Hairul Azhar; Al-Qdah, Malik T.; Chuah, Hean Teik; Tayahi, M. B.; Abdullah, Mohammad Khazani (Wiley Periodicals, 2006)
Optimization study of the Chromatic Dispersion measurement technique using relative power of two beating frequencies is presented in this paper. The performance of the CD measurement technique is studied in terms of the measurement range and sensitivity as the wavelength separation is varied. Based on the mathematical model and experimental results the technique sensitivity increases with wavelength separation. However, this increase in sensitivity is traded off with narrower measurement range. The measurement technique is optimized at 5.0 GHz wavelength separation with sensitivity of 0.009 (dB/ps/nm) and measurement range of 2500 (ps/nm). (c) 2006 Wiley Periodicals, Inc.